ORGANIZATION OF PRACTICAL LESSON FROM INTERNAL MEDICINE IN FOREIGN CITIZENS BY CASE-METHOD UNDER CREDIT-MODULE SYSTEM OF EDUCATION - Vakalyuk, I.I. (World of Medicine and Biology, 2013)
The successful organization of the educational process of foreign citizens on the internal medicine departments is possible under the active use of the case-method. It is found that the effectiveness of an objective examination of the patient according to the case history promotes deep clinical thinking of the student. At the final stage of practical lesson is appropriate presentation of the results and protection of case history, during which the teacher evaluates the work of each group and each student, including the parallel control questioning regarding etiologic and pathogenetic factors and clinical signs from the case. Determined the prospects of further search for the most optimal ways to combine modern international methods of educational process with the national methodological specificity.